MEMBANGUN TATA RUANG TERBUKA HIJAU MENUJU LINGKUNGAN SEHAT DAN ASRI : SEBUAH ANALISA PERSPEKTIF HUKUM PENATAAN RUANG - Dian Ferricha; Zulham Hakim (Universitas Islam Balitar, Blitar, 2017)
That the development and growth of the city / urban is so significant accompanied by the rapid transfer of land functions, has caused environmental damage that can reduce the carrying capacity of land in sustaining the lives of people in urban areas, so it is necessary to make efforts to maintain and improve the quality of the environment through the provision of open space adequate green.